Past landscapes of the Bay of Puck - Andrulewicz, Eugeniusz (Turystyka i krajoznawstwo, 2021)
The study presents the basic hydrological features of the Bay of Puck which have allowed for the emergence and development of a diverse flora and fauna, including a rich ichthyofauna. On the basis of research and scientific publications, as well as the memories of older fishermen and inhabitants of the region, its state in the 1950s and 1960s is described. The reasons for its degradation were analyzed, including the specific projects and economic decisions that led to unfavorable environmental change. Action taken to protect the bay mainly consists of organizing wastewater management within the catchment area. It is pointed out that the Bay of Puck is still too heavily burdened with an inflow of nutrients as well as tourist overexploitation. Pressure from developers and the modernization of ports and fishing harbors is growing. As a result, unfavorable landscape changes in the Bay of Puck are still taking place.